Prospective Review of Clostridioides difficile Testing Indications to Inform Local Laboratory Stewardship Initiatives - Noah Reich; Michael Payne; Azra Sharma; Sylvie Champagne; Marc G. Romney; Michelle Hinch; Victor Leung; Christopher F. Lowe (Elsevier, 2019)
Summary: We conducted a prospective chart review to determine the prevalence of and reasons for inappropriate Clostridioides difficile test-ordering at a tertiary care hospital. Inappropriate orders accounted for 54% of all tests. The two primary aetiologies of inappropriate test-ordering were an alternative reason for diarrhoea (34%) and an asymptomatic patient (20%). These results highlight the need to focus diagnostic stewardship of C. difficile testing on pre-analytical factors. Keywords: Clostridioides difficile, Infections, Diagnostic Stewardship, Pre-analytical, Laxative